2010
DOI: 10.1159/000320725
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-Release Dinoprostone Vaginal Pessary with Concurrent High-Dose Oxytocin Infusion Compared to Sustained-Release Dinoprostone Vaginal Pessary Followed 6 h Later by High-Dose Oxytocin Infusion for Labor Induction in Women at Term with Unfavorable Cervix: A Randomized Controlled Trial

Abstract: Objective: To compare the efficacy and safety of sustained-release dinoprostone vaginal pessary and concurrent high-dose oxytocin infusion with sustained-release dinoprostone vaginal pessary followed 6 h later by high-dose oxytocin infusion for cervical ripening and labor induction. Methods: A total of 500 nulliparous or multiparous women with a singleton pregnancy, Bishop score ≤4 and admitted for labor induction. Women were randomly assigned to induction of labor using intravaginal dinoprostone with concurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…concluded that oxytocin is less effective than vaginal and cervical prostaglandin E2 (PGE2) in bringing about vaginal delivery within 24 h; however, a recent Cochrane review of vaginal prostaglandin for induction of labor at term reported that prostaglandin was effective for inducing labor and to increase vaginal delivery rates . In addition, there are many protocols in the literature . suggesting the use of cervical priming agents and oxytocin together for IOL with poor Bishop scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…concluded that oxytocin is less effective than vaginal and cervical prostaglandin E2 (PGE2) in bringing about vaginal delivery within 24 h; however, a recent Cochrane review of vaginal prostaglandin for induction of labor at term reported that prostaglandin was effective for inducing labor and to increase vaginal delivery rates . In addition, there are many protocols in the literature . suggesting the use of cervical priming agents and oxytocin together for IOL with poor Bishop scores.…”
Section: Discussionmentioning
confidence: 99%
“…However, we know that dinoprostone can prime the cervix and cause contractions but its effect on augmentation is still a query. The longer median delivery time for the dinoprostonw group pointed out the need for concurrent or post‐retrieval use of effective induction agents . Data on the need for pre‐induction cervical priming for half‐ripened cervix Bishop scores (≥4 or ≤6) are scarce, and pre‐induction cervical ripening may not lower the cesarean delivery rate in nulliparas with an unfavorable cervix for this subgroup …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 103 trials identified, just 63 were RCTs. 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 The majority of RCTs were single-center trials conducted in academic hospitals, which can limit the generalizability of the results to other community-based populations. Among the 12 multicenter trials, the number of centers ranged from 2 to 49 and tended to include both university-affiliated and community hospitals.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
“…4,5 As normal labor depends on efficient myometrial contractions to efface and dilate a compliant cervix, when the cervix is unfavorable, administration of ripening agents is followed by intravenous infusion of oxytocin. 10 Recent randomized controlled trials have indicated that in the event of an unripe cervix, local application of PGs followed by oxytocin infusion is safer and more effective than oxytocin administration alone or concurrent with PGs 16,17 ; therefore, we sought to investigate in vitro the myometrial response to oxytocin after incubation with PGE1 and PGE2. Surprisingly, we found that PGs did not affect or even decreased myometrial response to oxytocin.…”
Section: Discussionmentioning
confidence: 99%